Transcriptional changes in LMH cells induced by Eimeria tenella rhoptry kinase family protein 17 - Meng, Yi-Jing; Mu, Bing-Jin; Liu, Xiao-Xin; Yu, Lin-Mei; Zheng, Wen-Bin; Xie, Shi-Chen; Gao, Wen-Wei; Zhu, Xing-Quan; Liu, Qing (Frontiers in Veterinary Science, 2022)
Though a number of Eimeria tenella rhoptry kinase family proteins have been identified, little is known about their molecular functions. In the present study, the gene fragment encoding the matured peptide of E. tenella rhoptry kinase family protein 17 (EtROP17) was used to construct a recombinant vector, followed by transfection into leghorn male hepatoma (LMH) cells. Then, the transcriptional changes in the transfected cells were determined by RNA-seq. The expression of EtROP17 in LMH cells was validated by both Western blot and indirect immunofluorescence analysis. Our analysis showed that EtROP17 altered the expression of 309 genes (114 downregulated genes and 195 upregulated genes) in LMH cells. The quantitative real-time polymerase chain reaction (qRT-PCR) results of the selected differentially expressed genes (DEGs) were consistent with the RNA-seq data. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that DEGs were significantly enriched in nine pathways, such as toll-like receptor signaling pathway, ECM-receptor interaction, intestinal immune network for IgA production and focal adhesion. These findings reveal several potential roles of EtROP17, which contribute to understanding the molecular mechanisms underlying the host-parasite interplay.